Endogenous Cerberus activity is required for anterior head specification in Xenopus - Silva, Ana Cristina (2018)
We analyzed the endogenous requirement for Cerberus in Xenopus head development. 'Knockdown' of Cerberus function by antisense morpholino oligonucleotides did not impair head formation in the embryo. In contrast, targeted increase of BMP, Nodal and Wnt signaling in the anterior dorsal-endoderm (ADE) resulted in synergistic loss of anterior head structures, without affecting more posterior axial ones. Remarkably, those head phenotypes were aggravated by simultaneous depletion of Cerberus. These experiments demonstrated for the first time that endogenous Cerberus protein can inhibit BMP, Nodal and Wnt factors in vivo. Conjugates of dorsal ectoderm (DE) and ADE explants in which Cerberus function was 'knocked down' revealed the requirement of Cerberus in the ADE for the proper induction of anterior neural markers and repression of more posterior ones. This data supports the view that Cerberus function is required in the leading edge of the ADE for correct induction and patterning of the neuroectoderm.